Developing a Compact Particle Collector by Integrating a Wet Electrostatic Precipitator and an Inertia Mist Eliminator - Zhengda Yang; Hongbo Qiu; Can Zhou; Ye Jiang; Riyi Lin; Yang Yang; Chenghang Zheng; Xiang Gao (Aerosol and Air Quality Research)
Abstract Wet electrostatic precipitator (WESP) is a reliable alternative to realize the ultra-low emission of particulate matter from coal-fired power plants. This work proposes to develop a compact particle collector by integrating a WESP and an inertia mist eliminator (IME). The particle collection efficiency and charging characteristics of the WESP were analyzed to determine the potential for compact design. Results show that the WESP was easy to achieve a collection efficiency of 95% for both pin and wire electrodes. Particle charging can still be guaranteed with short WESP length and high voltage, indicating the particle charging was sensitive to electrical parameters. Charges carried by the escaping particles acted as a bridge between the WESP and the IME. The collision enhanced by particle charging can lead to an improvement in overall efficiency and charge loss. The particle charge loss of the particle sized 7.29 µm was 22.6% and 29.4% for the one and two stage IME, which coincided with the efficiency enhancement of WESP. The collection efficiency significantly decreased as the WESP size decreased, but the collection efficiency can be enhanced by the combination with IME. The 6-wire WESP enhanced by one-stage IME can be considered the optimal combination because the WESP size can be shorten by 40% while maintaining a similar efficiency. The research findings are beneficial for the retrofit of air pollution control devices in limited space.